THE ECTOPIC ADRENAL CORTICES IN ONE HUMPED CAMEL - N.S., Al-Samarrae; F.J., Al-Saffar; A.H, Al-Tikrety (The Iraqi Journal of Veterinary Medicine, 1996)
The developing ectopic adrenal cortices from nodules. The nodules are embedded in the adrenal capsule, cortical parenchyma or even in the medullary zone of the adrenal gland. These nodules are encapsulated by connective tissue and consist of small polyhedral to columnar cortical cells.